Preferensi Tanaman Pakan Kupu-Kupu di Lingkungan Kampus IPB Dramaga, Bogor - Kadri, Muhammad; Noorchaliza, Fauzia; Yodhy, Lintang; Aminuddin, Syahras Fathin; Priawandiputra, Windra; Atmowidi, Tri (Jurnal Sumberdaya Hayati, 2025)
Butterflies are flower visitors and are important for plant pollinators. This research aimed to analyze the food plant preferences of butterflies and analyze the correlation between butterfly proboscis and flower corolla tube lengths.  Observations of butterflies were carried out at four locations within Dramaga campus area of Bogor Agricultural University from March to April 2024. The results showed 23 species of butterflies were observed on the flowers of eighteen plant species. Hesperiids and Nymphalids butterflies were found dominantly. The shrub plant, Lantana camara is the most visited by butterflies (8 species), followed by Saraca indica (6 species), and Turnera ulmifolia (5 species). Butterflies prefer to visit tubular shape and purple color of flowers. Based on the correlation analysis, there was no significant correlation between the butterfly proboscis and the flower corolla tube lengths.